Performance comparisons across pig farms - Davidov Ivana; Stevančević Ognjen; Božić Aleksandar; Galfi-Vukomanović Annamaria; Davidov Nikola (Biotechnology in Animal Husbandry)
Understanding the dynamics of swine health, including mortality rates during critical stages of development, is essential for improving overall productivity. The aim of this study was an examination of pig farms, focusing on performance metrics such as litter size, mortality rates among different age groups, and weight changes throughout the production cycle. The three farrowto-finish pig farms from South Bačka District were selected based on their willingness to participate and provide accurate records. The statistical analysis, including one-way ANOVA and post hoc tests, provided further evidence of significant differences among the farms in specific metrics. By analyzing the results in this study, it could be concluded the importance of optimizing breeding, feeding, and health management strategies to enhance swine production efficiency.